Inflammatory Characteristics of Monocytes from Pediatric Patients with Tuberous Sclerosis - Meyer, Claudius U.; Kurlemann, Gerhard; Sauter, Matthias; Wiemer-Kruel, Adelheid; Hahn, Andreas; Doganci, Aysefa; Birkholz, Julia; Faber, Jörg; Gehring, Stephan; Hertzberg, Christoph; Zepp, Fred; Knuf, Markus (Neuropediatrics, 2015)
Objective Therapeutic options for the tuberous sclerosis complex (TSC) syndrome showed varying outcomes. Malfunctional tsc1/tsc2 genes leave mTOR uninhibited, a positive downstream modulator of the innate proinflammatory immune system, which has not yet been described in pediatric patients with TSC.Methods Using polymerase chain reaction (PCR) gene expression levels of monocytes after cultivation with lipopolysaccharide (LPS) or with LPS + mTOR inhibitor rapamycin, patients with TSC (n = 16) were compared with healthy subjects (n = 20).Results Compared with monocytes from healthy controls, LPS showed a more prominent gene expression pattern in patients with TSC (CCL24, CXCL10, IL-6, IL-10, and IL-1B). Proinflammatory reactions against LPS were modulated by rapamycin. With LPS + rapamycin monocytes from patients with TSC showed gene expression patterns different from healthy subjects. Furthermore, developmental differences were discernible in patients with TSC, compared with gene expression levels for patients 0 to 5 years to those 6 to 11 years of age, the latter with marked expression of IL-6 IL-1A, IL-1B, RIPK2, but also IL-10.Conclusion The effects of LPS, even more of LPS with rapamycin on monocytes from patients with TSC suggested that inflammatory processes are distinct from those in healthy subjects. Furthermore, reaction to rapamycin indicates age-related gene expression levels. Our findings offer a model to decipher the unknown and varying gene expression pattern induced by rapamycin.
Keywords: tuberous sclerosis; inflammation; rapamycin; monocyte; children